Tawarruq in Islamic Law: an appraisal of its admissibility and criteria in the context of private transactions - Sadique, Muhammad Abdurrahman (Serials Publications, 2015)

(untitled)
Tawarruq is the purchase of a commodity that is in the ownership and possession of the seller against a deferred price, and its subsequent sale by the purchaser to a party other than the seller on cash, for the purpose of obtaining cash. Even though there has been some scholarly objection to its practice, the majority appear to have considered tawarruq to be within the boundaries of shari 18ah. Among those who have censured tawarruq, the absence of any school as a whole is noteworthy. Juristic criticism of tawarruq is seen to be principally based on the aspect of intention and motive, and the possibility that necessary requirements for validity may be left unfulfilled. It is incorrect to equate tawarruq with 18inah, and the motive of obtaining cash itself would not render tawarruq impermissible. The paper examines the nature and criteria for tawarruq with regard to its use by individuals in a non-institutional setup. The study finds that with fulfillment of the vital conditions, there can be no strong objection to individuals resorting to tawarruq for fulfilling their liquidity needs, especially in the absence of other means.